2001
DOI: 10.1007/s001250051627
|View full text |Cite
|
Sign up to set email alerts
|

A locus affecting obesity in human chromosome region 10p12

Abstract: Obesity is a multigenic trait that is a major risk factor for a number of common diseases, particularly Type II (non-insulin-dependent) diabetes mellitus, cardiovascular disease and hypertension. A recent review reported a total of 44 genomic locations with possible linkage to one or more obesity-related phenotypes [1]. Because false positive findings are common in genome scans for complex traits, replication is essential before undertaking gene identification studies. Previously, linkages for obesity traits h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 7 publications
(13 reference statements)
4
51
1
Order By: Relevance
“…We have previously reported in the French Caucasian population three regions of linkage with obesity on chro-mosomes 2, 5, and 10p, which have been confirmed in other ethnic groups (31,32). However, this first French sample set only included a small number (n ϭ 66) of sibships with both individuals possessing the severe form of obesity (BMI Ն35 kg/m 2 ), which in our view justified a specific and adequately powered genome-wide analysis focused at the more extreme end of the phenotype.…”
Section: Discussionsupporting
confidence: 63%
“…We have previously reported in the French Caucasian population three regions of linkage with obesity on chro-mosomes 2, 5, and 10p, which have been confirmed in other ethnic groups (31,32). However, this first French sample set only included a small number (n ϭ 66) of sibships with both individuals possessing the severe form of obesity (BMI Ն35 kg/m 2 ), which in our view justified a specific and adequately powered genome-wide analysis focused at the more extreme end of the phenotype.…”
Section: Discussionsupporting
confidence: 63%
“…Early reports indicated relatively consistent findings for 10p from three studies of US European American, French, and German cohorts. [19][20][21]63 Subsequently, several other reports on obesity-related phenotypes have found signals in the same or nearby chromosomal regions, but also including signals on 1q, 12 12,27 None of these studies have reported sex-specific linkage findings.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high heritability estimates in the range 0.43-0.64 have also been reported for BMI (Luke et al 2001;Perola et al 2001;Wu et al 2002;Brown et al 2003;Schousboe et al 2004), although lower estimates have also been reported (e.g., Platte et al 2003). There have been numerous genomewide scans of BMI, reviewed in Chagnon et al (2003), although only five genome scans report regions of linkage for BMI in African Americans (Price et al 2001;Kotchen et al 2002;Wu et al 2002;Zhu et al 2002;Palmer et al 2004).…”
Section: Introductionmentioning
confidence: 99%